2015
DOI: 10.1093/jcr/ucv057
|View full text |Cite
|
Sign up to set email alerts
|

Boomerang Effects of Low Price Discounts: How Low Price Discounts Affect Purchase Propensity

Abstract: We show that providing a low (vs. no) price discount can lower purchase propensity of low-priced products under certain conditions—when purchases are nonessential and purchase volume is small. Based on the theory of purchase value (Grewal, Monroe, and Krishnan 1998; Thaler 1983), we argue that offering a low price discount for nonessential purchases decreases perceived transaction value that in turn lowers consumers’ purchase propensity. However, this boomerang effect reverses when purchase volume is larger or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 15 publications
3
41
0
1
Order By: Relevance
“…We also asked participants to assess the quality of the product and the perceived seller opportunism using three items adapted from Cai et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also asked participants to assess the quality of the product and the perceived seller opportunism using three items adapted from Cai et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Consumers are easily influenced by the presentation formats of price‐based promotions (e.g., Cai et al., ; Chen, Monroe, & Lou, ; Kim, ; Krishna, Briesch, Lehmann, & Yuan, ). Prior research has revealed that various factors affect the appeal of promotional offers, and these factors include number representation (Kruger & Vargas, ); relative size of discount (Darke & Dahl, ); placement of prices (Choi & Coulter, ); and price‐item order (Bagchi & Davis, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…By being the first to investigate the relationship between resource scarcity and regulatory focus, we extend the marketing literature on the motivational impact of resource constraints (e.g., Cannon, Goldsmith, and Roux 2018;Kristofferson et al 2017;Laran and Salerno 2013;Mehta and Zhu 2016;Zhu and Ratner 2015). In addition to revealing a novel marketing consequence of resource scarcity, the current research contributes to the pricing literature (Ames and Mason 2015;Cai, Bagchi, and Gauri 2016;Janiszewski and Lichtenstein 1999;Monga and Bagchi 2012) by providing insights on the sociopsychological factors shaping consumers' attitudes toward range marketing offers and the underlying mechanism. From a managerial perspective, this research suggests potential tactics that companies can use to increase the acceptance and effectiveness of range marketing offers.…”
mentioning
confidence: 93%
“…Discount is not always a good choice for a promotion strategy. Cai et al (2016) illustrated this boomerang effect through the lens of purchase value theory, which argues that consumers' purchasing propensity is lower when a low discount is offered on nonessential products, and higher when the same discount is given on essential products. The mechanisms are bridged by perceived acquisition value and transaction value, which are different for consumers who are making decisions regarding essential and nonessential purchases.…”
Section: Marketing Strategymentioning
confidence: 99%